Scientific production in Scopus about use of ayahuasca in human health: A bibliometric analysis. - Gonzales Dávila, Kary (2022)
Introduction: Ayahuasca (also called huasca, oasca, caapi or yagé) is a concoction of traditional use, with psychoactive effects of interest in human health. This situation creates the need to generate scientific knowledge to identify gaps in knowledge and research priorities. Objective: To describe the impact of scientific production on the use of Ayahuasca in human health published in journals indexed in Scopus until October 2021. Methods: Bibliometric study of secondary databases. A systematic search of information was carried out in Scopus, in order to identify original articles that investigated the use of Ayahuasca in health problems. Information was collected on the year of publication, language of publication, areas of knowledge studied, research designs involved, journal of publication, proportions of international collaboration, inter-institutional collaboration networks, co-authorship networks, citations per document and the authors were described. more productive. Results: The trend of publications has been increasing since 2012. 36.8% of investigations were based on observational designs; with an average number of citations per article of 6.1 and an average number of citations per year of 3.9. All publications from Switzerland, China, New Zealand and Peru had international collaboration; with four cooperation conglomerates. Conclusion: The scientific production on the use of Ayahuasca in health has a growing trend, preferably in observational designs, with high international collaboration and institutional collaboration networks and authors.